UPAYA KEPALA SEKOLAH MENINGKATKAN KINERJA SEBAGAI LEADER DALAM MANAJEMEN MUTU TERPADU - Maria Ulfa; Shalahuddin Shalahuddin (STAI Sangatta Kutai Timur, 2023)
School performance is important to create a culture of integrated quality management. The purpose of this research is to analyze and describe the efforts of school principals in managing integrated management. The research method used in this research is qualitative, using a descriptive approach. Collecting data using observation techniques, documentation, observation, and interview techniques. Data analysis used qualitative data analysis with the stages of data collection, data reduction, and conclusion. Based on this research, shows that the performance of UPT SMPN 26 Gresik principals as leaders can create school members who can achieve the goals of the school's vision mission and strategic plans. The performance of the school principal as a leader is: 1) holding socialization of the vision and mission that has been formed, which includes the goals and strategic plans of the school to internal and external customers; 2) reinforcing motivation to educators and educational staff to optimally improve performance with measurable achievements; 3) carry out coaching activities for teachers and school administrative staff with a structural and familial approach so that they contribute positively to the development of school quality; and 4) providing facilities to educators and educational staff to develop themselves through activities, such as training and workshops. Here the principal is expected to be a strong, tough, and professional leader.